The economic valuation of urban green spaces as a voice in the debate over their role in sustainable cities - Piotr Czembrowski (Economic and Environmental Studies (E&ES), 2016)
Recognizing social preferences seems to be crucial for successful spatial planning of urban green spaces. Economic valuation is one way to recognize these preferences. In this paper I analyze and draw common conclusions from three hedonic pricing researches conducted recently in Łódz which reveal the economic potential of green spaces and highlight the multidimensionality of their value. These comparable studies analyze the impact of green spaces on apartment sale prices. Each of them emphasizes different attributes or features of green spaces, such as their area, social perception and biocultural value. Together they draw a complex picture of people's preferences towards urban green spaces and constitute the platform for further discussion on the role of green spaces in sustainable cities of the future.
Keywords: Q01; Q51; R32; 330; economic valuation; integrated valuation; hedonic pricing; urban green infrastructure; sustainable development